Chronic effects of exhausting exercise and overtraining on the immune response: Th1 and Th2 profile - Thiago Teixeira Guimarães; Rodrigo Terra; Patrícia Maria Lourenço Dutra (Desafio Singular, 2017)
Although physical inactivity figures as one of the main causes attributed to mortality, the damage caused by excessive exercise is also a reality. Professional athletes, amateur or uncompetitive modalities beneficiaries are often affected by deleterious conditions resulting from excessive exercise, such as neurological, endocrine and immune origin. The thin line between losses and benefits of successive fatiguing sessions effort depends on the understanding of concepts and methodological training principles. Exercise may have a paradoxical relationship and its consistent prescription in terms of public health depends on a better understanding of their cellular mechanisms. In this sense, the purpose of this review was to explore a promising topic in sports science, able to contribute to elucidate such mechanisms: Th1 and Th2 profile of the immune response related with chronic exhausting exercise and overtraining.